Effects of transmission shaft flexibility on rolling element bearing tribodynamics in a high-performance transmission. (November 2021) - Friskney, Brett; Mohammadpour, Mahdi; Theodossiades, Stephanos; Craig, Christopher; Rapson, Greg
Highlights: Rotordynamics are combined with local nonlinearities to study transmission dynamics. Nonlinearities and shaft flexibility significantly alter the response of the system. Additional resonance is introduced due to nonlinear bearing action. Flexible shafts reduce the size of load fluctuation transmitted to the bearings. Bearing life predictions are reduced as a result of the system-level analysis. Abstract: In a high-performance transmission, rolling bearings play a crucial role in supporting the loaded shafts and gear mesh whilst minimising friction. Prediction of critical speeds and dynamic responses is important to avoid prolonged periods of elevated vibration amplitudes, which can contribute to premature bearing and gearbox failure. Nonlinearities such as backlash and time-varying stiffnesses can lead to complex coupled dynamics between gears and bearings. In the current study, an 8-speed transmission is discretized and modelled by the finite element method. The eigenproblem is solved using damped modal analysis considering gyroscopic effects. Time-varying stiffness data and backlashes are introduced as nonlinearities. The system response is compared for cases of linear and nonlinear bearings, and rigid and flexible shafts to ascertain the significance of elasticity. The flexible model improves the accuracy of bearing load oscillation by altering the transfer path between gears and bearings. This provides an advancement upon existing works, where shaft dynamics are often simplified. Furthermore, it is shown that the combination of local nonlinear effects and flexible components significantly changes the response of the system and the bearing life prediction for a system-level analysis.